Design of a Central Wireless Security System Using Atmega328, ZigBee and Arduino - , Olumuyiwa O. Fagbohun; , Oyeyemi Mayowa Fagbohun (Archives of Current Research International, 2018)
Security of life and properties is one of the basic provisions of a nations constitution which must be well protected at all times. For residential and industrial setups, there are so many security infractions that needed better solutions taken the advantages of the new developments in Communication technology. This work intends to provide a security system to monitor a residential or industrial setup, for infractions and give the necessary information to arrest its effect even without the physical presence of the property owner. The design consists of wireless sensor network for surveillance in a typical residential or industrial outfit using ZigBee wireless communication protocol, while the ATTiny102 microcontroller was used as the controller for the sensor and security module. The information from the ZigBee wireless device was transmitted through a radio frequency signal at 2460 MHz to the central processing unit with ATmega328p microcontroller to give information received through a buzzer alarm and SMS notification including an LCD display. The result shows a cost-effective means of securing a property at all times, while giving a clear reception of signals at distance of < 500 m from the central controlling unit, with total harmonic distortion [THD] calculated as 2.37%, and the measured THD with the use of a distortion analyzer between 1.29% and 3.63% at a separated distance of 500 m. The signal noise was calculated as 1.79dB, while the measured signal noise was 1.52dB and 2.34dB. The signal strength is about 72% of the maximum derivable of -42.7dBm from the system propagation at 500m distance apart, while the efficiency is calculated to be 96.7% with ease of maintenance due to few components used.